Quercus ilex forests are influenced by annual variations in water table, soil water deficit and fine root loss caused by Phytophthora cinnamomi - Corcobado, Tamara; Cubera, Elena; Moreno, Gerardo; Solla, Alejandro (Agricultural and Forest Meteorology, 2013)
Itishypothesised thatmajor reductions intree vitality are related tomarked changes insoilwater content, extremely wet winters followed by dry summers, and the presence of pathogenic organisms which take advantage of this situation. This study helps clarify the role of annual variations in water table, soil water content and ﬁne root abundance in the decline of Quercus ilex forests, with special focus on trees growing in Phytophthora cinnamomi-infested soils. Conducted in western Spain, the study included 5 Q. ilex dehesa stands in which tree water status and soil water dynamic were compared in declining and non-declining trees, and 96 additional stands in which ﬁne root abundance and pathogen assessment were compared in declining and non-declining trees. Declining trees showed signiﬁcantly lower values than non-declining trees for leaf water potential and stomatal conductance. The period of waterlogging (2 months maximum, ﬂuctuating from −0.5 to −4.5m), the soil water content values observed in summer (signiﬁcantly higher in declining trees) and the similar presence of Pythium spiculum in declining and non-declining trees are not sufﬁcient in themselves to explain tree health status. However, ﬁne root density was 16.2% lower in declining than non-declining trees and 42% lower in P. cinnamomi-infected than non-infected trees. Root damage caused by P. cinnamomi in combination with periods of saturated soils favourable for the pathogen but unfavourable for the tree, coupled with small-scale differences in soil water-holding capacity, explain the symptoms and water status of declining trees. The combination of root damage and water stress explained above-ground symptoms of declining trees and will probably determine tree survival.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Oak decline; Open woodlands; Root density; Root-rot disease; Saturated soil; Water deﬁcit

Effects of Mediterranean dehesa management on epiphytic lichens. - Aragón, Gregorio; López, Rubén; Martínez, Isabel (The Science of the total environment, 2010)
Spanish holm oak (Quercus ilex subsp. ballota) open woodlands (dehesas) maintain a high diversity of plants and animals compared to other forested Mediterranean habits, but little is known about the responses of epiphytic lichens to different management regimes that are applied to this woodland type. The present study was carried out in central-southern Spain and included four management regimes: agriculture, grazing of sheep, grassland grazed by wild ungulates (deer), and abandoned dehesas covered by shrubs. Total species richness and cover exhibited considerable variation among management regimes. Both parameters tended to decrease with the intensity of management, abandoned dehesas maintaining a higher number of species than more intensively managed habitats. Lichen composition also significantly differed among the four regimes. Nitrophytic species were clearly associated with more intensive management regimes (farming or livestock management), whereas non-nitrophytic species favored abandoned dehesas.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 20937519
Keywords: Lichen composition; Mediterranean Spain; Nitrophytic specie; Open woodlands; quercus ilex subsp. ballota; s Management regime